Exposure to maternal fuels during pregnancy and offspring hepatic fat in early childhood: The healthy start study. Issue 7 (5th February 2022) - Cohen, Catherine C.; Francis, Ellen C.; Perng, Wei; Sauder, Katherine A.; Scherzinger, Ann; Sundaram, Shikha S.; Shankar, Kartik; Dabelea, Dana
Summary: Background: Intrauterine overnutrition has been associated with paediatric nonalcoholic fatty liver disease (NAFLD), but the exact mechanisms involved remain unclear. Objective: To examine whether maternal fuels and metabolic markers during pregnancy are associated with offspring hepatic fat in childhood. Methods: This analysis included 286 mother–child pairs from the Healthy Start Study, a longitudinal pre‐birth cohort in Colorado. Fasting blood draws were collected in early pregnancy (~17 weeks) and mid‐pregnancy (~27 weeks). Offspring hepatic fat was assessed by magnetic resonance imaging (MRI) at ~5 years. Results: In early pregnancy, maternal triglycerides (TGs) and free fatty acids (FFAs) were positively associated with offspring hepatic fat [Back‐transformed β (95% CI): 1.15 (1.05, 1.27) per 1 standard deviation (SD) TGs; 1.14 (1.05, 1.23) per 1 SD FFAs]. Maternal total cholesterol (TC) and low‐density lipoprotein cholesterol (LDL‐C) were also associated with offspring hepatic fat, but only among boys [1.22 (1.08, 1.37) per 1 SD TC; 1.21 (1.07, 1.37) per 1 SD LDL‐C]. In mid‐pregnancy, only maternal TGs remained associated with offspring hepatic fat. Adjusting for potential confounders or mediators did not affect associations. Conclusions: Maternal lipid concentrations, especially in early pregnancy, are associated with higher offspring hepatic fat, and may, therefore, be targeted in future interventions among pregnant women.